1996
DOI: 10.1007/bf00448801
|View full text |Cite
|
Sign up to set email alerts
|

Malignant melanoma of the conjunctiva: occurrence and survival following surgery and radiotherapy in a Danish population

Abstract: The results are estimated to represent a nationwide sample of patients. No prognostic factors of significance were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 13 publications
2
60
0
4
Order By: Relevance
“…Clinical prognostication Institution- 42,43 and populationbased [44][45][46] retrospective studies have consistently shown that the location and size of the primary conjunctival melanoma are strong and independent predictors of prognosis. Primary tumours located at the limbus, their most common site, or displaced to the cornea 47 carry a better prognosis than tumours in the bulbar, caruncular, and palpebral conjunctiva.…”
Section: Prognosis Of the Primary Tumourmentioning
confidence: 99%
“…Clinical prognostication Institution- 42,43 and populationbased [44][45][46] retrospective studies have consistently shown that the location and size of the primary conjunctival melanoma are strong and independent predictors of prognosis. Primary tumours located at the limbus, their most common site, or displaced to the cornea 47 carry a better prognosis than tumours in the bulbar, caruncular, and palpebral conjunctiva.…”
Section: Prognosis Of the Primary Tumourmentioning
confidence: 99%
“…Notably, only one of our patients required exenteration, which has been necessary in up to 20% of patients in other studies. 15,32 Our patient requiring exenteration was referred in 1995 after treatment elsewhere and we had treated her with adjunctive cryotherapy, which we have since abandoned.…”
Section: Eyementioning
confidence: 99%
“…Sua incidência vem aumentando nos Estados Unidos da América entre a população masculina (20,21) e em pacientes acima de 60 anos (21) . MC é mais frequente em indivíduos idosos com idade média va riando de 55 a 70 anos (6,18,19,(22)(23)(24)(25) . Embora raro em jovens, existem relatos de casos de MC em pacientes com menos de 20 anos de idade (26,27) .…”
Section: Incidênciaunclassified
“…Embora raro em jovens, existem relatos de casos de MC em pacientes com menos de 20 anos de idade (26,27) . Não existe diferença significativa entre o acometimento de homens e mulheres (6,18,19,(22)(23)(24)(25) .…”
Section: Incidênciaunclassified